IMPLEMENTATION OF E-PROCUREMENT IN GOVERNMENT PROCUREMENT POLICY AT POLDA METRO JAYA - Edgar Firman Illahi; Mardi Aman (SEAN Institute, 2023)
E-procurement is used to make purchases of goods and services. This study's objective is to determine what variables Polda Metro Jaya's Procurement Service Unit must consider while implementing procurement rules for electronic goods and services. The data gathered for this study was repeatedly and thoroughly checked using qualitative methods. The study's findings suggest that this application can be utilized to make purchasing of goods and services simpler. The e-procurement deployment was done correctly based on the idea of policy implementation.